2017
DOI: 10.22159/ajpcr.2017.v10i12.22065
|View full text |Cite
|
Sign up to set email alerts
|

Recent Reports on Pyrazole-Based Bioactive Compounds as Candidate for Anticancer Agents

Abstract: Pyrazole is a five-membered heterocyclic compound containing two nitrogen atoms. Due to its biological significance, design of novel pyrazole derivatives has become an interesting research area. We report the current progress in the development of anticancer agents containing pyrazole ring covering the time span of the past few years (2013)(2014)(2015)(2016). The presence of this nucleus is accompanied with some side chains, functional groups, or in combination with other nucleus such as thiazole, thiourea, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Numerous 5‐aminopyrazole derivatives occupy a key place in medicinal, pharmaceutical, and agrochemical industry such as antibacterial, antifungal, antileishmanial, anticancer, antidepressant activity, and anti‐inflammatory . Also, they considered as noncompetitive GABA antagonists and insecticides, potent human A 2 B adenosine receptor antagonist, and anti‐tobacco mosaic virus activity .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous 5‐aminopyrazole derivatives occupy a key place in medicinal, pharmaceutical, and agrochemical industry such as antibacterial, antifungal, antileishmanial, anticancer, antidepressant activity, and anti‐inflammatory . Also, they considered as noncompetitive GABA antagonists and insecticides, potent human A 2 B adenosine receptor antagonist, and anti‐tobacco mosaic virus activity .…”
Section: Introductionmentioning
confidence: 99%
“…Those isolated compounds have been reported to have a high anticancer activity [13][14][15]. In regard to mechanism of action, several recent studies reported that alkaloids have the ability to promote apoptosis through inducing DNA damage [16][17][18]. Other isolated compounds can also be expected to contribute to the anticancer activity possessed by marine sponge Calthropella sp.…”
Section: In Vitro Mtt Cytotoxic Assay Of Fractionmentioning
confidence: 99%
“…[3][4][5] Amongst heterocyclic compounds, nitrogen-containing heterocycles are extensively found as a core framework in a huge library of heterocycles and show several employments in natural science and other areas of science. 6 Additionally, nitrogen-containing heterocycles have striking structural features and they are widely observed in natural products, for instance, vitamins, hormones and alkaloids. 7,8 Pyrazole 1 is known to be one of the most potential families of nitrogen-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole derivatives exhibit a broad spectrum of biological profiles, for instance, anti-tubercular, 9 anti-AIDS, 10 anti-malarial, 8 * For correspondence anti-microbial, 11 antitumor, 12,13 anticancer 14 and antifungal. 6 In addition, pyrazoles have also been found as promising anti-hyperglycemic, 15 anti-depressant, 16 anti-convulsant, 17 anti-pyretic, 18 anti-anxiety 19,20 and insecticidal agents. 21 Bipyrazole shows diuretic, cytotoxic and cardiovascular efficacy.…”
Section: Introductionmentioning
confidence: 99%